DESAIN MEJA SETRIKA LIPAT UNTUK UMKM LAUNDRY DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Puput Rahmawati; Rizqi Ramadhani; Damang Suhdi Lubis (Jurnal Inkofar, 2022)
The growth of laundry every year will increase by 20% and reach 50% in 2022. In the laundry washing process, the process of ironing and folding clothes is a process that requires the most energy and long time. Constraints that occur in the process of ironing and folding clothes cause overload so that many laundries refuse customer requests causing the resulting turnover to be not optimal. The folding ironing table innovation can combine the functions of ironing as well as folding clothes in one process. The Quality Function Deployment (QFD) method is used to get the voice of the customer and build the House of Quality (HOQ) matrix. Customers desire an ironing board product that has strong and sturdy material, ergonomic design, wide table size, flexible and multifunctional, quality base, and has an attractive design. The development of a folding ironing table product design with a strong and sturdy material, specifically stainless steel, as well as an ironing table base that can be rotated and folded flexibly is expected to make the process of ironing and folding clothes more effectiveKeywords : laundry, ironing, folding clothes, Quality Function Deployment, House of Quality